Design and modeling of Klann mechanism-based paired four legged amphibious robot - Rafeeq, Mohammed; Toha, Siti Fauziah; Ahmad, Salmiah; Mohd Yusof, Muhammad Syafiq; Mohd Razib, Mohd Asyraf; Shamsul Bahrin, Muhammad Ikmal Hakim (IEEE, 2021)
The ability of the amphibious robot to walk on dry land and swim in the water motivates many researchers to explore the structural design strategies and control methods of the system. In this research, the paired four-legged amphibious robot is designed and modeled. The optimized Klann linkage mechanism is applied as the mechanism of the robot's leg. The kinematic analysis of the designed model is performed in SAM (Simulation and Analysis of Mechanisms) to study the motion trajectory of the system. The inverse dynamic analysis is used to obtain the driving torque of the actuator for the designed amphibious robot. The results demonstrate that the trajectory path of the lower part of the foot in the Klann mechanism is more horizontal than the four-bar mechanism and resulting in higher propulsion of the Klann mechanism than the four-bar mechanism. The simulation also reveals that the amphibious robot has the capability to maneuver and thus validate the ability of the designed model.